RESILIENCE OF ADOLESCENT POST-DISASTER ERUPTION OF MOUNT SEMERU: LITERATURE REVIEW - Rahmawati, Primasari Mahardhika; Suhari, Suhari; Astuti, Anggia; Musviro, Musviro (Universitas Airlangga, 2021)
Introduction:Indonesia sits on an active continental plate, surrounded by a series of very active volcanoes called the ring of fire. These conditions make Indonesia very vulnerable to disasters. Mount Semeru was observed to have experienced at least 57 eruptions or eruptions. The resilience possessed by adolescents can affect when the post-eruption disaster strikes.Methods:The strategy to determine the selection of studies that have been found, the author uses a protocol and evaluation uses the PRISMA Checklist and is adjusted to the purpose of this literature review. Searching for literature sources in this literature review uses several databases including PubMed and Google ScholarResults:Resilience is very important for adolescents in post-mountain eruption disaster situations, adolescents who have resilience can survive and never give up in difficult circumstances, adapt to these conditions, and can rise. Most of the adolescents in post-disaster areas have moderate levels of resilience as much as 64% and as high as 63%. This can occur due to several factors, namely individuals, families, and communities. In addition, gender can also affect a person's resilience. Men are more resilient than women.Conclusion:The existence of sources of support from internal and external as well as knowledge about adolescent disasters can optimize youth resilience after the Semeru eruption disaster.